Fabrication and analysis of ZnO nanoflower and nanorod structures to improve superhydrophobicity using myristic acid - Ban Hamdan Al-Mulla; Haider Abdulelah; A. Nawabjan; S.M. Hussin; Ahmad Irfan; Md. Ferdous Rahman (Results in Physics)
This study investigates the improvement of superhydrophobicity in ZnO nanoflowers and nanorods through modification with myristic acid (MA). ZnO nanostructures were synthesized via hydrothermal and sol–gel methods, then combined with varying MA weight percentages (2–20 %) to create a ZnO/MA composite. X-ray diffraction and FTIR analyses confirmed the crystalline structure of ZnO and the bonding between ZnO and MA. FESEM imaging showed the nanoflower and nanorod morphologies of ZnO covered with MA. The optimal results revealed that MA-modified ZnO NFs and NRs achieved maximum water contact angles of 166° and 158°, respectively, indicating that MA’s shorter carbon chain can produce a denser coating, enhancing superhydrophobic properties and offering potential for self-cleaning applications.